The relationship between sources of power and dimensions of transformational leadership in private sectors / Nor Farhana Abdullah and Nur Aziyati Saidin - Abdullah, Nor Farhana; Saidin, Nur Aziyati (Faculty of Business and Management, 2013)
Most organization experienced changes due to globalization must evolve in other to survive. The era of globalization, organization needs better prepared to be transform from the old culture to new culture. Organization that usually had rapid technological changes, globalization, and increase in competition and changing markets will directly give challenge and impact to organizational leaders. Hersey and Blanchard (1996) believe that leaders should be flexible and alter their styles as followers and situations change. At present, leader may use all different power to lead their employees towards successful goals. Leadership is a power relationship that exists between leaders or followers (Northhouse, 2001) and a process which involves utilising power to influence others behaviours to meet the organisational goals (Handy, 1993). Any movements whether backward or forward usually related with the good or weak leader. Good leader will transform the people and employees with positive attitude and behavior and weak leader unable to influence and direct followers to intended goals. Moreover, a leader can be a role model to someone else. When people see the positive criteria possessed by a leader, they will usually take it as an example to be follows. Many recent writers on leadership have emphasised the importance of the leader empowering others to reach their own potential (Mullins, 2002). Ability to ask people to do work or task on behalf of yourself is called as power. A leader needs a power to influence them to follows them and this only happen when the right power use to control them. According to Hersey et al. (2001) states that leaders who understand and know how to use power are more effective than those who do not or will not use power. Power can be divided into five categories which are coercive power, reward power, expert power, legitimate power and reference power. Strong organization relies on the leaders’ direction and employee contribution to it. Transformational leader needs to be competitive enough to carry out the effectiveness in the organization by changes in culture changes and motivating activities. So, this research will study which source of power can give impact towards transformational leadership.